How the Cold War ended : debating and doing history - Prados, John (Issues in the history of American foreign relations., 2011)
The Cold War continues to shape international relations almost twenty years after being acknowledged as the central event of the last half of the twentieth century. Interpretations of how it ended thus remain crucial to an accurate understanding of global events and foreign policy. The reasons for the Cold War's conclusion, and the timing of its ending, are disputed to this day. In this concise introduction to the Cold War and its enduring legacy, John Prados recognizes the debate between those who argue the United States was the key player in bringing it to a close and those who maintain that American actions were secondary factors. Like a crime scene investigator meticulously dissecting evidence, he applies a succession of different methods of historical analysis to illuminate the key cataclysmic events of the 1980s and early 1990s from a range of perspectives. He also incorporates evidence from European and Soviet intelligence sources into the study. The result is a stunning narrative that redefines the era, embraces debate, and deconstructs history, providing a coherent explanation for the upheavals that ended the conflict. How the Cold War Ended also provides an in-depth guide to conducting historical inquiries: how to choose a subject, how to frame a narrative, and how to conduct research and draw conclusions. Prados does this for a variety of methods of historical analysis, furnishing a how-to guide for "doing history" even as it explores a crucial case study. - Publisher